Mechanical chest compressions in the coronary catheterization laboratory - do not hesitate to go step further - Bělohlávek, Jan; Kovárník, Tomáš (Scandinavian journal of trauma, resuscitation and emergency medicine, 2016)
Authors Wagner et al. in your journal demonstrated effectiveness of mechanical chest compressions in the coronary catheterization laboratory to facilitate coronary intervention and survival in patients requiring prolonged resuscitation efforts. We dare to comment on this article and advocate to use mechanical chest compressions only as a bridge to extracorporeal membrane oxygenation to completely substitute failed circulation and enable percutaneous coronary intervention or other procedures to treat the cause of cardiac arrest.
Keywords: masáž srdce; hrudník; Cardiopulmonary Resuscitation; Thorax; Percutaneous Coronary Intervention; srdeční zástava; Humans; Heart Arrest; Heart Massage; lidé; kardiopulmonální resuscitace; koronární angioplastika